Kristin Olafson-Jenkyns: The Culinary Saga of New Iceland (Recipes from the Shores of Lake Winnipeg) - Semple, Ann (Petits Propos Culinaires, 2024)
Kristin Olafson-Jenkyns: The Culinary Saga of New Iceland (Recipes from the Shores of Lake Winnipeg): Coastline Publishing, Guelph, Ontario: 32 Canada; 23.00 US.